Kesesuaian Penyimpanan Vaksin Covid-19 Di Instalasi Farmasi Di Salah Satu Dinas Kesehatan Bengkulu - Yanti, Sari; Misa Ayu Lia Sari (Gayaku Publisher, 2024)
Vaccine management is an inseparable part of service. Every service unit must manage vaccines properly according to vaccine management guidelines as a quality of service. Vaccines which are included in freeze sensitive vaccines and heat sensitive vaccines, if not stored at the perfect temperature, can cause loss of vaccine potency. The purpose of this study was to review how the Covid-19 vaccine preparations were stored at the Bengkulu Health Office. This research uses an observational design with a checklist & interview method for retrospective data collection with a cross sectional approach. The instruments or tools used in this research are a checklist, interview list of questions and primary data on activities for storing Covid-19 vaccine preparations in the pharmaceutical installation warehouse of the Bengkulu Health Service.The results of the research show that the storage of Covid-19 vaccines at the Bengkulu health service has met the requirements but is still not entirely in accordance with good drug distribution methods and Minister of Health Regulation number 12 of 2017, namely that there are storage maintenance indicators that do not meet the requirements.